Pediatric demyelinating diseases of the central nervous system and their mimics : a case-based clinical guide - Waubant, Emmanuelle L.; Lotze, Timothy E. (Springer, 2017)
This collection of pediatric clinical cases focus on multiple sclerosis, neuromyelitis optica, acute disseminated encephalomyelitis and mimics. Dedicated sections on diseases affecting the brain, brainstem, spinal cord and the optic nerve feature chapters that include the diagnostic work up, therapeutic management and case outcome. Typical and atypical presentations of various pediatric demyelinating diseases also emphasize therapy response and those that breakthrough on treatment. Filling a critical gap in the literature on inflammatory disorders of the central nervous system, all those that treat patients with these rare and challenging disorders will find this book extremely helpful for their daily clinical practice.